Dental patents in India: A decade long review - Joe Mathew Cherian; Shannon Samuel; Abi M Thomas; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: The advent of technology in dentistry compels the safeguard of intellectual property to guarantee a steady flow of ideas. A guarantee preserves the idea/invention which is conductive to the subsequent financial gain or marketing of the said product for the patentee. The main objective of the present study was to illuminate the trends in the dental patents filed in India over the past decade and to analyze these in context with the recent developments in dental markets. Methodology: A total of 641 dental patent applications retrieved from the Indian Government Official Website between 2010 and 2020 were scanned for field of invention, type or status of application along with details regarding date of publication or filing of application, etc., The dataset was collaboratively analyzed using Panda's Library in Python software as analysis tool for data preparation and frequency analysis. The estimates were presented as mean differences and 95% confidence intervals. Results: The results showed that Indian Patent Office (IPO) has granted 54 dental patents in the last decade. The maximum applications of the IPO processes are the patent co-operation treaty National Phase applications (53.3%), mostly in the bio-engineering field (36.8%). Chiefly, patents were filed by individuals and companies (n = 180) and average time for grant was 4.90 years and 5.34 years, respectively. Conclusion: The process of patent application in India although has become digitalized needs to be more comprehensible and time bound, with more awareness disseminated to entrepreneurs and dental students alike.